Verapamil-Sensitive Idiopathic Left Ventricular Tachycardia in a 6-Month-Old. Issue 1 (January 2015) - Hiremath, Gurumurthy; Li, Walter; Foltz, Rhonda; Roy-Burman, Arup; Cocalis, Mark; Tanel, Ronn E
<x xml:space="preserve">Abstract</x> Abstract Idiopathic left ventricular tachycardia of the Belhassen type is rare in infants. We present a 6-month-old infant girl with a wide-complex tachycardia with right bundle branch block QRS morphology, a superior axis, and atrioventricular dissociation, consistent with a left anterior fascicular tachycardia. Initial echocardiogram revealed depressed ventricular function. The tachycardia was unresponsive to therapeutic trials of adenosine, esmolol, procainamide, and lidocaine. There was brief conversion of the tachycardia to sinus rhythm with transesophageal atrial overdrive pacing, suggesting a reentrant mechanism of the arrhythmia. Ultimately, the judicious administration of intravenous verapamil resulted in termination of the arrhythmia, which has been sustained on oral therapy.